Efficacy and safety of SPRINT and STAR protocol on Malaysian critically-ill patients - Ahamad N.; Razak N.; Jamaluddin U.; Suhaimi F.; Pretty C.; Chase G.; Ralib A.; Noor B.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Biomedical engineering; Intensive care units; Safety engineering; Stars; Control protocols; Critically-ill patients; Hyperglycaemia; Hypoglycaemic; Insulin infusions; Model based controls; Model-based OPC; Patient safety; Patient treatment